2007
DOI: 10.1016/j.neuropharm.2007.02.013
|View full text |Cite
|
Sign up to set email alerts
|

NMDA inhibitors cause apoptosis of pyramidal neurons in mature piriform cortex: Evidence for a nitric oxide-mediated effect involving inhibitory interneurons

Abstract: Pyramidal relay neurons in limbic cortex are vulnerable to denervation lesions, i.e. pyramidal neurons in layer IIα of piriform cortex undergo transsynaptic apoptosis after lesions that interrupt their inputs from the olfactory bulb. We have previously established the role of inhibitory interneurons in elaborating signals that lead to the apoptosis of projection neurons in these lesion models, i.e. the upregulation of neuronal NOS and release of nitric oxide. Thus, we have proposed that cortical interneurons p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Under conditions of excessive activation of the NMDA receptor, NO synthesized in the cytosol by the action of nNOS may initiate both cytosolic and nuclear apoptotic signaling (Garthwaite et al, 1989;Dawson et al, 1991;Bonfoco et al, 1996). As recently shown by us (Koliatsos et al, 2004;Zhou et al, 2006;Zhou et al, 2007) and others (Corso et al, 1997;Parathath et al, 2007), similar processes can be signaled between neurons, i.e. nNOS-expressing interneurons can provide the source of NO that can diffuse and initiate apoptotic cascades in adjacent projection neurons.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Under conditions of excessive activation of the NMDA receptor, NO synthesized in the cytosol by the action of nNOS may initiate both cytosolic and nuclear apoptotic signaling (Garthwaite et al, 1989;Dawson et al, 1991;Bonfoco et al, 1996). As recently shown by us (Koliatsos et al, 2004;Zhou et al, 2006;Zhou et al, 2007) and others (Corso et al, 1997;Parathath et al, 2007), similar processes can be signaled between neurons, i.e. nNOS-expressing interneurons can provide the source of NO that can diffuse and initiate apoptotic cascades in adjacent projection neurons.…”
Section: Introductionsupporting
confidence: 60%
“…Nitric oxide (NO) is a molecular messenger with prominent roles in neuronal signaling (Garthwaite et al, 1988;Gally et al, 1990;Edelman and Gally, 1992;Schuman and Madison, 1994;West and Grace, 2000) but may also initiate or contribute to neuronal cell death (Nowicki et al, 1991;Zhou et al, 2007). As a diffusible gas that can cross membrane barriers within 100-micrometer distance (Wood and Garthwaite, 1994;Philippides et al, 2000), NO is ideally suited to modulate synaptic plasticity in a spatially constrained fashion (Dawson and Snyder, 1994;Schuman, 1994;Esplugues, 2002;Sunico et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, ketamine-induced release of glutamate in anterior cingulated cortex (ACC) is correlated with positive psychotic symptom scores in healthy human subjects ( r = 0.72) (Stone et al, 2012). Furthermore, NMDAR antagonists play known roles in neurodegenration and excitotoxicity, including apoptosis of mature corticolimbic pyramidal cells (Zhou et al, 2007; Farber and Olney, 2003; Horváth et al, 1997; Wozniak et al, 1998), thus offering NMDAR hypofunction as a possible basis for brain atrophy observed in schizophrenia (Rais et al, 2012; Andreone, et al, 2007; Rais et al, 2008; Goldman et al, 2007; Ferrari et al, 2006). …”
Section: Evidence For Nmdar Dysfunctionmentioning
confidence: 99%
“…NO can permeate the plasma membrane and destroy post-synaptic structures via the generation of reactive oxygen species within the dendrites and cell body. Therefore, NO especially nNOS induction and activation of layer I interneurons may be a common denominator linking lesion-and NMDA antagonist-induced death of pyramidal neurons in limbic cortex (Zhou et al, 2007).…”
Section: Tablementioning
confidence: 99%